Is Anti-Suppression the Quest for Visibility? - Hussey, Eric (Optometry & Visual Performance, 2015)
Vision science defines the fundamental action of the vision system to be the generation of visible percepts. Intermittent central suppression (ICS) is an intermittent, usually alternating, loss of visual sensation, a repetitive loss of that visual percept. A review of the vision science literature on visibility, Troxler's Perceptual Fading, and the consequences of loss of visibility suggests that loss of visual motion signal causes loss of visibility. The area of lost visibility is then filled in by a cortical computation mechanism. Fixation, binocular saccades, vergence, and sensory perception are all compromised in loss of visibility. Some of the characteristics of ICS, as well as suspected consequences of ICS, have been difficult to reconcile with the conventional wisdom on suppression. That conventional wisdom suggests that suppression is solely a function of cortical inhibition. Those ICS characteristics and consequences may be better explained if ICS is viewed as a loss of visibility from Troxler's Fading. Fixation changes and perceptual changes with loss of visibility parallel findings in ICS and the vision- and-dyslexia literature. Research methods to reverse loss of visibility parallel treatment methods for ICS. These parallels suggest that loss of visibility may be diagnosed clinically as ICS, and ICS should be treated with a goal of ensuring bilateral visibility, that is, binocularity.